2002
DOI: 10.1103/physrevlett.88.185003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Verification of the Shear-Modified Ion-Acoustic Instability

Abstract: The predicted shear-induced shift of the wave phase velocity, the essence of the shear-modified ion-acoustic (SMIA) instability mechanism that reduces ion Landau damping for otherwise damped ion-acoustic waves [V. Gavrishchaka et al., 80, 728 (1998)], is verified with direct measurements in a strongly magnetized laboratory plasma. The SMIA growth rate is shown to increase with increasing shear, as predicted. SMIA wave propagation is shown to be possible at both small and large angles to the magnetic field, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…The parallel flow velocity difference equivalent to ∆V ie ≥ 1 V, which leads the instability to be excited in our experimental condition, corresponds to the shear parameter σ 2 ≥ 20, and this value is much larger than σ 2 = 1 ~ 2 in the case of the shear-modified ion-acoustic instability reported previously [10]. In our synthesized plasma, no parallel electron drift flow (electron current) is actually generated, so that the large parallel shear is needed to give rise to the instability in the presence of only the ion drift flow, the velocity of which is much less than that of electrons.…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…The parallel flow velocity difference equivalent to ∆V ie ≥ 1 V, which leads the instability to be excited in our experimental condition, corresponds to the shear parameter σ 2 ≥ 20, and this value is much larger than σ 2 = 1 ~ 2 in the case of the shear-modified ion-acoustic instability reported previously [10]. In our synthesized plasma, no parallel electron drift flow (electron current) is actually generated, so that the large parallel shear is needed to give rise to the instability in the presence of only the ion drift flow, the velocity of which is much less than that of electrons.…”
Section: Resultsmentioning
confidence: 41%
“…In the parallel shear case, some experimental investigations related to parallel-flow-shear driven instabilities, such as the D'Angelo mode [6][7][8], ion-acoustic [9,10], and ion-cyclotron [11][12][13] instabilities, have been performed in various situations. In these experiments, it is to be noted that the instabilities are excited by a slight amount of parallel shear in the presence of the parallel electron current which often exists in conventional configurations such as Q machine experiments [14], and therefore it is very difficult to experimentally evaluate the precise value of the parallel shear, which leads to difficulty in understanding the effects of the parallel shear on these instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was studied (Gavrishchaka et al, 1998(Gavrishchaka et al, , 2000, and experimentally demonstrated (Teodorescu et al, 2002;Agrimson et al, 2001). A transverse gradient is naturally present in an EIC wave structured electron flow because the electron drift is energized by EIC wave fields: in one phase the drift is upgoing, in another it is downgoing, and the opposing drifts are separated by λ ⊥ /2.…”
Section: Discussionmentioning
confidence: 99%
“…In the right half plane, however, the wave amplitude appears to be strangely small, which is likely to result from an inevitable plasma-disturbance by the probe insertion into the plasma. For estimation of axial wave number k z the "Y-shaped probe" consisting of two Langmuir probes on the two tips with the separation d is adopted, enabling us to detect a relative wave phase difference δθ(ψ) between the two tips, where ψ is a probe-array/magnetic-field orientation angle [14]. Figures 3(a) and 3(b) illustrate a schematic of the Y-shaped probe measurement and a typical shape of measured δθ(ψ), respectively.…”
Section: Experimental Apparatusmentioning
confidence: 99%